Business investment in EU countries - Marta Bańbura; Maria Albani; Gene Ambrocio; Dirk Bursian; Ginters Buss; Jasper de Winter; Miroslav Gavura; Claire Giordano; Paulo Júlio; Julien Le Roux; Matija Lozej; Sune Malthe-Thagaard; et al. (European Central Bank (ECB), 2018)
The article analyses recent developments in business investment for a large group of EU countries, using a broad set of analytical tools and data sources. We find that the assessment of whether or not investment is currently low varies across benchmarks and countries. At the euro area level and for most countries, the level of business investment is broadly in line with the level of overall activity. However rates of capital stock growth have slowed down since the crisis. The main cyclical determinants of investment developments in the euro area include foreign and domestic demand, uncertainty and financial conditions. Uncertainty seems to have played a negative role during the financial and sovereign debt crises; however, given its low levels more recently, it has not acted as a drag on business investment overall during the recovery. Credit constraints appear to have hindered investment during the twin crises, especially in stressed countries. Aside from cyclical developments, important secular factors - relating to demographics, the changing nature and location of production, and the business environment - have influenced investment. Another factor that may have amplified the decline in private investment, particularly in countries that were hit hardest by the sovereign debt crisis, is the low level of public investment. This is because when public investment enhances the productivity of the private sector, there may be positive spillovers from the former to the latter, including across countries. Finally, intra-sector capital misallocation, measured as the within-sector dispersion across firms in the marginal revenue product of capital, has been increasing in Europe since 2002, which may in turn have exerted a significant drag on total factor productivity dynamics, and hence on aggregate output growth.
Keywords: E32; E52; E62; D24; D61; 330; business investment; uncertainty; monetary policy; capital misallocation